Adaptive programming in multi-level cell ReRAM. (August 2019) - Ramadan, Misbah; Wainstein, Nicolás; Ginosar, Ran; Kvatinsky, Shahar
Abstract: Resistive memory (ReRAM) is an attractive technology to replace Flash technology and/or serve as a new memory tier. When a fixed programming voltage is applied to the resistive cell (memristor), its resistance changes logarithmically in time. This is undesirable for using the memristors as a multi-level cell (MLC) memory. We present Adaptive Programming (AP) – a feedback-based programming circuit and method that improve process variation tolerance and uniformity of MLC levels, by effectively linearizing the memristive behavior. An appropriate sneak-path current mitigation has been identified as well. AP requires fewer programming steps than other programming methods, resulting in 46% faster programming and 95% energy reduction. AP reduces the frequency of errors (FoE) by 50% as compared to other writing schemes. Furthermore, AP enables using the memristors as a multi-level counter facilitating multi-valued computing arrays for non-von Neumann machines.